GEOGRAPHY AND GENDER IN TEACHERS' UNIONS OF PRESIDENTE PRUDENTE (SP): THE LIMITS OF OFFICIAL UNIONISM - Silva, Jane Rosa da [UNESP]; Paula, Ricardo Pires de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
The article aims to contribute to the discussions on the participation of women in teachers unions in Presidente Prudente (SP) from a geographic perspective. Therefore, we delimited the study to three unions: Union of Workers in the Municipal Public Service (SINTRAPP), Teachers Union of Official Education in Sao Paulo State (APEOSP) sub thirst of Presidente Prudente and Union of Workers in Presidente Prudente Education Institutions (SINTEE-PP). Understanding that gender discussion is fundamental in society, especially in essentially feminine activities, as is the case of teaching profession, we will study how this theme is inserted within the limits of official unionism. In this sense we point that the fragmentation (corporate-categories-territorial) characteristic of the State unionism in Brazil, is a limit to the unified action of workers, as well as, for performing discussions about the gender issue in the teachers unions.
Keywords: gender; Geography of gender; teachers' union; State unionism